2016
DOI: 10.15376/biores.11.1.2723-2733
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Fast-Growing Aspen Alkaline Peroxide Mechanical Pulp Lignin: A Post-Enzymatic Treatment

Abstract: An enzymatic mild acidic hydrolysis was used to separate and purify residual lignin from alkaline peroxide mechanical pulp (APMP). Using the optimum conditions for the laccase treatment (pH 4.5, temperature 50 °C, lignin consistency of 1%, a reaction time of 60 min, and a laccase dosage of 8 μ/g), oven-dried lignin was treated with laccase and in a laccase mediator system (LMS) to explore the mechanism for laccase and the LMS modification of APMP. The changes of functional groups in lignin were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As described by Wang et al in 2016, the oxidation of lignin with LMS can lead to a degradation of the lignin by the fact that Cβ of the β-O-4 functional groups decreased. 11,37 Additionally, a study by Potthast et al in 1999 demonstrated the fact that LMS polymerizes phenolic substrates. Depending on the time of the polymerization process, LMS can also degrade the formed polymers which was shown by a time-dependent measurement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As described by Wang et al in 2016, the oxidation of lignin with LMS can lead to a degradation of the lignin by the fact that Cβ of the β-O-4 functional groups decreased. 11,37 Additionally, a study by Potthast et al in 1999 demonstrated the fact that LMS polymerizes phenolic substrates. Depending on the time of the polymerization process, LMS can also degrade the formed polymers which was shown by a time-dependent measurement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…L P and L S were isolated and refined by the enzymatic-mild acidic hydrolysis method (Jääskeläinen et al 2003;Guerra et al 2006). This isolation process could give the isolated lignin the characteristics of higher yield, higher purity and minor structural changes (Guerra et al 2006;Wang et al 2016). Lignin was isolated according to the procedure shown in Figure 1.…”
Section: Lignin Isolationmentioning
confidence: 99%
“…Interestingly, the total amounts of sidechain substructures in lignin structure dramatically decreased after steam explosion pretreatment, particularly in L L which had dissolved in the steam-exploded liquid during the steam explosion process. It is noteworthy that there were substituents on C α in the β-O-4′, β-β′, β-5′ and β-1′ linkages, so the main reason for decreases in these four structures could be explained by the destructive effect of the C α cationization on the binding bond (Wang et al 2016). In addition, lignin is a polymer sensitive to high temperature and acidic environment, and under these conditions, depolymerization and repolymerization occur, as shown in Figure 6 (Li et al 2007).…”
Section: Quantification Of Lignin Structuresmentioning
confidence: 99%